SOSIALISASI PERANCANGAN AUGMENTED REALITY UNTUK PENGENALAN HARDWARE BERBASIS ANDROID STUDI KASUS SMA KI HAJAR DEWANTORO - Umi Khaerunnisa; Wulan Pahira; Gusmayeni (Abdi Jurnal Publikasi, 2025)
This activity aims to provide education and training to high school students at SMA Ki Hajar Dewantoro on utilizing Augmented Reality (AR) technology in Android-based computer hardware learning. AR technology enables students to visualize computer hardware components, such as the motherboard, processor, and RAM, in 3D. Through this interactive approach, students can more easily understand the functions and mechanisms of each component, which are often taught theoretically and lack deep understanding. The implementation of AR is expected to serve as a teaching aid that not only enhances students' understanding but also strengthens their motivation to explore technology further. The partner for this activity is SMA Ki Hajar Dewantoro, located in Tangerang. Based on interviews with the school, it was found that students face difficulties in understanding hardware concepts because teaching has largely been theory-based with limited practical experience. The school also faces constraints in providing the necessary tools and physical equipment for hands-on practice, making computer hardware learning less optimal. Therefore, the application of AR is seen as a solution to these limitations, offering students a richer and deeper learning experience. The expected outcomes of this activity include improved student understanding of computer hardware components, increased learning motivation, and the establishment of a more interactive learning pattern. The methods for the activity include introducing AR technology, training on using AR applications, hands-on practice by students, and conducting discussions and evaluations. Evaluation techniques involve questionnaires and interviews to measure changes in students' understanding and motivation before and after the activity. Data analysis is conducted qualitatively through interviews. The output of this activity includes the development of AR-based learning modules for sustainable use by the school, improvement in the quality of computer hardware education, and heightened student motivation to study technology.